THE EFFECT OF NATRIUM BICARBONATE (NaHCO3)AND TEMPERATURE ON THE QUALITY OF DURIAN SEED TORTILLA ( Durio zibethinus Murr) - Budi Suarti; Misril Fuadi; Wira Dian Rasih (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
This study uses a complete random design (CRD) with a factorial (2) two replications. The first factor is the amount of sodium bicarbonate with a password (N) consisting of 4 levels, namely: N0 = 0%, 0,1% = N1, N2 and N3 = 0,2% = 0,3%. The second factor is the temperature of the drying with a password (S) which consists of 4 levels, namely: S1 = 550C, 600C = S2, S3 = 650C and S4=700C. The parameters observed were: carbohydrate content, water content, organoleptic color, and texture. In this study, the best treatment to make tortillas durian seed is the N3S4 treatment, the amount of 0.3% sodium bikarbnat and drying temperature 700C. Keywords: tortilla, durian seed, sodium bicarbonate, drying temperature